Electrical safety assessment according to Bangladesh national building code (BNBC) - Zawad, Sakib Mohammed; Alvi, Md. Hasin; Hossain, Mohammad Imam; Chowdhury, Muammer Zaman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.